2019
DOI: 10.1111/crj.13108
|View full text |Cite
|
Sign up to set email alerts
|

Favorable survival even with high disease‐specific complication rates in lymphangioleiomyomatosis after lung transplantation—long‐term follow‐up of a Japanese center

Abstract: Background: Lung transplantation (LT) is a reliable therapeutic option for end-stage pulmonary lymphangioleiomyomatosis (LAM). Long-term outcome of LAM recipients after LT remains unknown. The aim of this study was to describe the outcomes of LT for LAM with a long-term follow-up, comparing those for other diseases in the same period. Methods: We retrospectively reviewed consecutive 145 LT recipients between 1998 and 2015 at Okayama University Hospital with minimum 3-year follow-up. Results: Twelve LAM recipie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Positive outcomes were also reported by two retrospective studies in a German and a Japanese centre even if the latter found a high rate of LAM-related complications in long-term follow-up (e.g. chylothorax, pneumothorax and LAM recurrence) [71,72].…”
Section: Lammentioning
confidence: 78%
“…Positive outcomes were also reported by two retrospective studies in a German and a Japanese centre even if the latter found a high rate of LAM-related complications in long-term follow-up (e.g. chylothorax, pneumothorax and LAM recurrence) [71,72].…”
Section: Lammentioning
confidence: 78%
“…Lung transplant for LAM is relatively rare; however, it is associated with better post-transplant survival compared to other advanced lung diseases. (1,(303)(304)(305)(306)(307) Fewer patients with LAM have required lung transplant since the standardized use of mTOR inhibitors as treatment, but it remains an indication for those with severely abnormal lung function (FEV 1 < 30%), exertional dyspnea (NYHA class III or IV), or hypoxemia at rest. (303)(304)(305)(306)(308)(309)(310)(311)(312)(313)(314)(315) While disease recurrence does occur post-transplant, it does not appear to limit survival.…”
Section: Lymphangioleiomyomatosis (Lam)mentioning
confidence: 99%
“…(1,(303)(304)(305)(306)(307) Fewer patients with LAM have required lung transplant since the standardized use of mTOR inhibitors as treatment, but it remains an indication for those with severely abnormal lung function (FEV 1 < 30%), exertional dyspnea (NYHA class III or IV), or hypoxemia at rest. (303)(304)(305)(306)(308)(309)(310)(311)(312)(313)(314)(315) While disease recurrence does occur post-transplant, it does not appear to limit survival. (303,304,309,311,(316)(317)(318) Where organ availability allows, bilateral lung transplant may be favored given the risk of post-transplant pneumothorax in the native lung; however, single lung transplant confers similar overall survival based on limited data.…”
Section: Lymphangioleiomyomatosis (Lam)mentioning
confidence: 99%
See 1 more Smart Citation
“…An important issue to consider is that these patients usually have had a prior pleural procedure, which can cause a large amount of bleeding during transplantation. The use of mTOR inhibitors in patients being considered for transplantation remains a matter of debate, but the current consensus is that they should be used until transplantation is considered, and the patient should be thoroughly educated about the risks involved [ 63 - 65 ].…”
Section: Disease-specific Guidelinesmentioning
confidence: 99%